Location and Electronic Nature of Phosphorus in the Si Nanocrystal − SiO(2) System - König, Dirk (Sci Rep, 2015)
Up to now, no consensus exists about the electronic nature of phosphorus (P) as donor for SiO(2)-embedded silicon nanocrystals (SiNCs). Here, we report on hybrid density functional theory (h-DFT) calculations of P in the SiNC/SiO(2) system matching our experimental findings. Relevant P configurations within SiNCs, at SiNC surfaces, within the sub-oxide interface shell and in the SiO(2) matrix were evaluated. Atom probe tomography (APT) and its statistical evaluation provide detailed spatial P distributions. For the first time, we obtain ionisation states of P atoms in the SiNC/SiO(2) system at room temperature using X-ray absorption near edge structure (XANES) spectroscopy, eliminating structural artefacts due to sputtering as occurring in XPS. K energies of P in SiO(2) and SiNC/SiO(2) superlattices (SLs) were calibrated with non-degenerate P-doped Si wafers. [Image: see text] results confirm measured core level energies, connecting and explaining XANES spectra with h-DFT electronic structures. While P can diffuse into SiNCs and predominantly resides on interstitial sites, its ionization probability is extremely low, rendering P unsuitable for introducing electrons into SiNCs embedded in SiO(2). Increased sample conductivity and photoluminescence (PL) quenching previously assigned to ionized P donors originate from deep defect levels due to P.